Baytoushi's evidence in the double prepositions in his book ((Sarf u Alhenaya fe kashf u Alkyfaya) Between grammatical thought and literary taste - أمير رفيق عولا المصيفي; هبة الله محمد شفيع رسول الديلزي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
There is no doubt that Abu Abdulla al-Baytoushi (1211 AH) was a grammarian scientist who edited a system in Arabic letters entitled "adequacy of meanings in the letters of meanings" and then explained it with a great title ( Al Hyfya be Tawthih Al Kyffaya) and then he writes another book entitled (SarfuAlhenayafekashfuAlkyfaya). The interpretation of the meanings of this book in verses of poetry organized by himself evidence of several grammatical issues concerning the meanings of letters, and these verses are characterized by precision in the evidence, and easiness in his style , which raises the grammatical thought and literary taste at the same time, It combines deep grammatical thinking with sober literary style Poetic verses move the mind and passion together. The grammarians raises in two things: First: making himself a witness grammar, and this is what we find not only a little among grammarians. The second is to investigate literary taste when making grammatical evidence. In this research, we want to highlight the deep grammatical ideas possessed by Baytoushi in the systems of those evidences in the letters and the passionate emotion he possesses in their systems in a literary style. To combine the grammatical thought and literary taste.